Кримінальний закон як засіб охорони прав і свобод людини в сучасному світі - Гальцова, В. В.; Haltsova, V. V.; Харитонов, С. О.; Kharytonov, S. O.; Храмцов, О. М.; Khramtsov, O. M.; Житний, О. О.; Zhytnyi, O. O.; Васильєв, А. А.; Vasiliev, A. A.; ORCID: http://orcid.org/0000-0001-9480-7814 (Вісник Національної академії правових наук України. - 2021. - Т. 28, № 3. - С. 248-256, 2021)
Надано аналіз теоретичних та прикладних питань, що стосуються засобів захисту прав людини та законних інтересів проти суспільно небезпечних посягань, а також формулювання науково обґрунтованих пропозицій щодо вдосконалення чинного законодавства України та практики його застосування у цій сфері. Виявлено правові характеристики прав і свобод людини як на національному, так і на міжнародному рівнях. Засоби захисту прав були продемонстровані через приціл кримінального права. Проаналізовано форми впровадження міжнародної практики у національне законодавство України як засіб захисту прав і свобод людини в сучасному світі.

This paper is a comprehensive study of the problems of criminal law as a remedy for human rights and freedoms in the modern world. The relevance of this subject lies in the systematic violations of constitutional human rights and freedoms and the inaction of the criminal law in such cases. Nowadays, the criminal law as a remedy for human rights and freedoms in national and international law is described by imperfection in its adaptation to rapidly changing social relations, which, accordingly, leads to problems in their legal protection. There are various reasons for this in the legal sphere, such as gaps in the legal provisions, conflicts of legal regulation and inconsistency of the rules of legislation with existing public relations in the state. All of the above determines the relevance of the subject matter of this study. Thus, the purpose of this study was a comprehensive analysis of theoretical and applied issues relating to the remedies for human rights and legitimate interests against socially dangerous encroachments, and the formulation of scientifically sound proposals for improving the current legislation of Ukraine and the practice of its application in this area. Ultimately, this study identified the legal characteristics of human rights and freedoms at both the national and international levels. The remedies for rights were demonstrated through the lens of criminal law. In addition, the study analysed the forms of implementation of international practice in the national legislation of Ukraine as a remedy for human rights and freedoms in the modern world. The significance of the results of this study was expressed in the further research of related subjects concerning this issue, namely the history of the development of EU criminal law standards and the historical establishment of the concept of human and citizen rights and legitimate interests. Furthermore, the materials of this study can be used in the preparation of educational materials, methodological recommendations, as well as training in various fields of legal science. This, in turn, will allow properly using the criminal law protection of human rights and freedoms without violations on the part of criminal justice bodies.

Представлен анализ теоретических и прикладных вопросов, касающихся средств защиты прав человека и законных интересов против общественно опасных посягательств, а также формулирование научно обоснованных предложений по усовершенствованию действующего законодательства Украины и практики его применения в этой сфере. Выявлены правовые характеристики прав и свобод человека как на национальном, так и международном уровнях. Средства защиты прав были продемонстрированы через прицел уголовного права. Проанализированы формы внедрения международной практики в национальное законодательство Украины как средство защиты прав и свобод человека в современном мире.
Criminal law as a means of protecting human rights and freedoms in the modern world
Гальцова, В. В. Кримінальний закон як засіб охорони прав і свобод людини в сучасному світі / Вікторія Володимирівна Гальцова, Сергій Олександрович Харитонов, Олександр Миколайович Храмцов, Олександр Олександрович Житний, Андрій Анатолійович Васильєв // Вісник Національної академії правових наук України. - 2021. - Т. 28, № 3. - С. 248-256. - DOI: 10.37635/jnalsu.28(3).2021.248-256.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне законодавство; criminal law; уголовное законодательство; права людини; human rights; права человека; міжнародна практика; international practice; международная практика; засоби правового захисту; means legal protection; средства правовой защиты; публічно-правова охорона; public legal protection; публично-правовая охрана